2020
DOI: 10.3233/jad-200393
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease-Like Neurodegeneration in Porphyromonas gingivalis Infected Neurons with Persistent Expression of Active Gingipains

Abstract: Background: Porphyromonas gingivalis (P. gingivalis) and its gingipain virulence factors have been identified as pathogenic effectors in Alzheimer's disease (AD). In a recent study we demonstrated the presence of gingipains in over 90% of postmortem AD brains, with gingipains localizing to the cytoplasm of neurons. However, infection of neurons by P. gingivalis has not been previously reported. Objective: To demonstrate intraneuronal P. gingivalis and gingipain expression in vitro after infecting neurons deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 52 publications
4
75
0
2
Order By: Relevance
“…Ilievski et al [8] have proven the concept that chronic periodontal infection can result in the formation of the diagnostic neuropathology lesions consistent with AD. Haditsch et al [9] confirmed the findings of Ilievski et al [8] for p-Tau on Ser396 and additionally demonstrated an increased tau phosphorylation at Thr231 following P. gingivalis infection with persistent gingipain expression with ongoing neurodegeneration.…”
Section: Porphyromonas Gingivalis Dna In Brain Microgliasupporting
confidence: 59%
See 1 more Smart Citation
“…Ilievski et al [8] have proven the concept that chronic periodontal infection can result in the formation of the diagnostic neuropathology lesions consistent with AD. Haditsch et al [9] confirmed the findings of Ilievski et al [8] for p-Tau on Ser396 and additionally demonstrated an increased tau phosphorylation at Thr231 following P. gingivalis infection with persistent gingipain expression with ongoing neurodegeneration.…”
Section: Porphyromonas Gingivalis Dna In Brain Microgliasupporting
confidence: 59%
“…As mentioned, Haditsch et al [9] reported AD-like neurodegeneration in P. gingivalis infected neurons in an in-vitro culture system with persistent expression of active gingipains. Following infection with live P. gingivalis (ATCC 33277) 25% of the neurons were lost in a time-dependent manner.…”
Section: P Gingivalis Infection Promotes Neurodegenerationmentioning
confidence: 89%
“…It was recently reported that gingipain inhibition reduces the bacterial load of an established P. gingivalis brain infection, decreases neuroinflammation, and rescues neurons in the hippocampus, revealing that this endopeptidase has a pivotal role in the mechanism of brain damage induced by P. gingivalis (34). Gingipains are likely to participate in the process of neuronal tissue invasion (38).…”
Section: Detection Of P Gingivalismentioning
confidence: 99%
“…Interestingly, the possibility that the immune response induced in the brain might differ depending on the infecting capsular P. gingivalis serotype has never been exploited. Microglia are known to discriminate against different bacterial antigens, triggering the activation of divergent pathways according to the antigens recognized ( 35 38 ). Thus, it is possible that some P. gingivalis strains might be more virulent than others in causing Alzheimer´s like-disease.…”
Section: Introductionmentioning
confidence: 99%
“…These are independent signals as only two genes are in both of these sets. A recent study by Haditsch et al, found that neurons derived from human inducible pluripotent stem cells, when infected with P. gingivalis , had a significant loss of synapse density (Haditsch et al 2020a) . This loss was more pronounced than neuron cell death.…”
Section: Discussionmentioning
confidence: 99%